2023
DOI: 10.1126/sciadv.adg5332
|View full text |Cite
|
Sign up to set email alerts
|

A reusable, impurity-tolerant and noble metal–free catalyst for hydrocracking of waste polyolefins

Abstract: One-step conversion of low-purity polyolefins to value-added products without pretreatments represents a great opportunity for chemical recycling of waste plastics. However, additives, contaminants, and heteroatom-linking polymers tend to be incompatible with catalysts that break down polyolefins. Here, we disclose a reusable, noble metal–free and impurity-tolerant bifunctional catalyst, MoS x -Hbeta, for hydroconversion of polyolefins into branched liquid al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…However, there is not a clear trend between AAR and molecular weight as the PS5300 oil’s AAR is comparable to that of the PS35 oils while the PS6000 oil’s AAR is ∼50% lower than the latter two, demonstrating a lower activity for PS6000. The differences in the virgin PS reactivities could stem from molecular weight, architecture, or viscosity, , and slip agents or other performance additives may be present and inhibit the deconstruction. , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is not a clear trend between AAR and molecular weight as the PS5300 oil’s AAR is comparable to that of the PS35 oils while the PS6000 oil’s AAR is ∼50% lower than the latter two, demonstrating a lower activity for PS6000. The differences in the virgin PS reactivities could stem from molecular weight, architecture, or viscosity, , and slip agents or other performance additives may be present and inhibit the deconstruction. , …”
Section: Resultsmentioning
confidence: 99%
“…The differences in the virgin PS reactivities could stem from molecular weight, architecture, or viscosity, 21,60 and slip agents or other performance additives may be present and inhibit the deconstruction. 17,25 Hydrogenolysis of commercial PS products (Figure 9c) shows a wide variability in reactivity. Rigid PS products (i.e., Petri dish and F-tube) produce clear, inviscid oils with high AARs, indicating significant hydrogenation and deconstruction (Figure 9d).…”
Section: Ni/sio 2 Catalystmentioning
confidence: 99%
See 1 more Smart Citation
“…The exponential surge in plastic consumption and waste accumulation, with polyolefins alone constituting 70% of the total, poses a global environmental challenge. The C–C backbone in polyolefins makes them durable as consumer goods but resistant to degradation after service life. Upcycling polyolefin wastes into value-added fuels represents a promising approach, including the hydrocracking technique that employs a bifunctional metal-acid catalyst and produces highly branched gasoline, diesel, and jet fuels. , …”
Section: Introductionmentioning
confidence: 99%
“…However, excessive low-value gas products were produced during the cracking process using the aforementioned monofunctional cracking catalysts. 23 Subsequently, bifunctional catalysts, such as Ru/HZSM-5, 24 MoS x -Hbeta, 25 Pt/Beta, 26 Rh–Nb 2 O 5 , 27 et al , offered both cracking and hydrogenation activities, have been reported for the catalytic degradation of polyolefin plastics. The polyolefin molecules were cleaved by the acidic sites of bifunctional catalysts via a carbocation reaction pathway, resulting in the generation of small molecular products.…”
Section: Introductionmentioning
confidence: 99%